Pengembangan Agroekowisata Berbasis Perkebunan Kopi Rakyat di Kecamatan Tutur, Kabupaten Pasuruan - Jojok Dwiridotjahjono; Ahmad Zainul Arifin; Purnomo Edi Sasongko; . Maroeto; Wahyu Santoso (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
IbW program’s aims to organize and plan the model of agrotourism development in Tutur Sub-District, Pasuruan District, based on the people's coffee. The several methods of implementation include socialization is done by several methods ranging from discourse, discussion, practice, module making, role play, and evaluation. The model approaches to the action program include: 1) Participatory Rural Appraisal (PRA) model; 2) Entrepreneurship Capacity Building model (ECB); and 3) Technology Transfer model (TT). In addition, advocacy program is conducted regularly between the companion with Manunggalig Karso farmer group, Tutur Sub-district, Pasuruan District. The results of the activities of IbW Agroekowisata in Tutur Sub-District, Pasuruan District based on coffee plantation of the people, have been achieved such as: a) Agricultural people garden profile in the form of audio visual; b) Detailed spatial plan for tourism areas of coffee garden and coffee house production, in the form of maps and floor plans; c) Banner and backdrop location of Desa Wisata Kopi; d) Guest book; and e) Design of location signposts. There are several reasons that encourage a positive response during the implementation of IbW: 1) IbW programs provide the economical benefits of integrated farming of coffee, apple, chrysanthemum, and dairy cattle; 2) Community empowerment methods and strategies implemented in this activity is a very effective facilitation felt by the community, especially promotion in the form of tourist visit book, flyer & brochure of coffee agro-tourism product, and website; and 3) The involvement of various elements can create synergism between the components concerned so that empowerment runs intensively and productively which has implications for the sustainability of the program.